Position of the illegitimate children under Islamic and civil law in Malaysia / Elisa Jantai, Siti Azyrnna Mohd Azani and Nurul Ashikin Baharudin - Jantai, Elisa; Mohd Azani, Siti Azyrnna; Baharudin, Nurul Ashikin (2010)
This academic project will focus on the position of the illegitimate child under Islamic Law and Civil Law. Subsequently, this research will be strengthening and supporting by the Holy Quran, Hadith, the opinion of the different School of thought and legal sources. The library research, reviewing relevant document, interview and internet were the tools employed for data gathering purposes. The finding indicate that the illegitimate child has a certain positions in Islamic Law and Civil Law such as the position in the parenting, maintenance and custody, marriage and position in the inheritance of the illegitimate child. Other legal positions that also will be viewed in this research are leading the prayer, giving testimony and funeral prayer of the illegitimate child.